A modified laparoscopic ureterolithotomy by pulling ureter with Carter–Thomason fascial closure and ureter incision by broken 15th blade. (September 2014) - Choi, H.; Kim, J. H.; Park, J. Y.; Shim, J. S.; Bae, J. H.
Background and Aims: To evaluate the efficacy and safety of a modified laparoscopic ureterolithotomy for the treatment of upper ureteral stones; this method involved the use of a Carter–Thomason fascial closure device, a broken 15th blade. Material and Methods: From February 2009 to December 2012, 38 patients with unilateral upper ureteral stones were examined and classified into 2 groups: one group underwent conventional laparoscopic ureterolithotomy (n = 21) and the other group underwent modified laparoscopic ureterolithotomy (n = 17). The modified laparoscopic ureterolithotomy consisted of the use of a Carter–Thomason fascial closure to extract the black silk along with the nylon tape. The ureter incision was made with a modified instrument consisting of a needle holder with a broken 15th blade tip. Results and Conclusions: Patient demographics were similar in both groups. No significant differences were detected between the conventional laparoscopic ureterolithotomy and modified laparoscopic ureterolithotomy groups with respect to operating time, estimated blood loss, and stone clearance rates. Drain-indwelling times were significantly shorter in modified laparoscopic ureterolithotomy patients than in conventional laparoscopic ureterolithotomy patients (3.2 ± 1.3 vs 4.7 ± 1.5 days). Hospital stay was significantly lesser in modified laparoscopic ureterolithotomy patients than in conventional laparoscopic ureterolithotomy patients (4.3 ± 1.2 vs 5.2 ± 1.2 days). No differences were detected in the ureteral stent indwelling time for the two groups. The use of the Carter–Thomason fascial closure facilitated ureter handling, and the use of a needle holder with a broken 15th blade tip enabled a sharp and precise ureteral incision. Our method allows early removal of the drain and thus earlier patient discharge.